2000
DOI: 10.1093/ptj/80.4.336
|View full text |Cite
|
Sign up to set email alerts
|

Work-Related Musculoskeletal Disorders in Physical Therapists: Prevalence, Severity, Risks, and Responses

Abstract: Background and Purpose. Physical therapists are at risk for work-related musculoskeletal disorders (WMSDs). Little is known of how therapists respond to injury or of what actions they take to prevent injury. The purpose of this study was to investigate the prevalence and severity of WMSDs in physical therapists, contributing risk factors, and their responses to injury. Subjects. As part of a larger study, a systematic sample of 1 in 4 therapists on a state register (n=824) was surveyed. Methods. An 8-page ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

51
433
19
35

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 333 publications
(579 citation statements)
references
References 28 publications
51
433
19
35
Order By: Relevance
“…West and Gardner [7] reported that 16% of physiotherapists first experienced their injury as students, whereas 56% reported their worst injury to have occurred within the first 5 years of working as a physiotherapist. The most common region of injury is the low back [3,4,6,7]. In our study, only 17.7% of physiotherapy students had never experienced LBP.…”
Section: Discussionmentioning
confidence: 50%
See 4 more Smart Citations
“…West and Gardner [7] reported that 16% of physiotherapists first experienced their injury as students, whereas 56% reported their worst injury to have occurred within the first 5 years of working as a physiotherapist. The most common region of injury is the low back [3,4,6,7]. In our study, only 17.7% of physiotherapy students had never experienced LBP.…”
Section: Discussionmentioning
confidence: 50%
“…To the best of our knowledge, this was the first study that clearly demonstrated the association between undergraduate physiotherapy study and LBP. There are many reports in the literature concerning the burden of work-related musculoskeletal injuries in physiotherapists [3][4][5][6][7]. West and Gardner [7] reported that 16% of physiotherapists first experienced their injury as students, whereas 56% reported their worst injury to have occurred within the first 5 years of working as a physiotherapist.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations